2017
DOI: 10.1590/1414-431x20165540
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefits of interferon-based therapy in patients with recurrent hepatitis C after orthotopic liver transplantation

Abstract: Recurrent hepatitis C after orthotopic liver transplantation (OLT) is universal and can lead to graft failure and, consequently, reduced survival. Hepatitis C treatment can be used to prevent these detrimental outcomes. The aim of this study was to describe rates of hepatitis C recurrence and sustained virological response (SVR) to interferon-based treatment after OLT and its relationship to survival and progression of liver disease through retrospective analysis of medical records of 127 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…Another unique factor involving LT patients is the occurrence of graft rejection. The rates observed in the present study with DAA were dramatically lower than a previous study at the same institution with interferon-based therapy (0 vs 48.6% of patients treated, with 38.9% of the rejection episodes considered to be related to interferon therapy) (32). The only rejection case (2% of the 55 patients included) was diagnosed 12 weeks after EOT.…”
Section: Discussioncontrasting
confidence: 84%
“…Another unique factor involving LT patients is the occurrence of graft rejection. The rates observed in the present study with DAA were dramatically lower than a previous study at the same institution with interferon-based therapy (0 vs 48.6% of patients treated, with 38.9% of the rejection episodes considered to be related to interferon therapy) (32). The only rejection case (2% of the 55 patients included) was diagnosed 12 weeks after EOT.…”
Section: Discussioncontrasting
confidence: 84%
“…Similarly, Chen et al [ 114 ] concurred that HCV genotype 1 was less likely to achieve SVR than non- genotype 1 infection. Zanaga et al [ 115 ] reported higher SVR with genotype 3 and statistically significant association with SVR on a univariate analysis in post-liver transplant population. A systematic review and a meta-analysis reported pooled SVR12 of 90% with simeprevir (SMV) and SOF combination with or without RBV in recurrent genotype 1 in post liver transplant population.…”
Section: Liver Transplant Recipientsmentioning
confidence: 99%